Adsorption Performance of Regenerated Molecular Sieves for Moisture Removal in Compressed Oxygen Gas - M. Baqir; Maulana, Fahrul; Nugraha, Asep; Hidayat, Rachmat; Jakariya; F, Zaeturohmah (Scientific Contributions Oil and Gas, 2026)
This study focuses on evaluating the adsorption performance of regenerated molecular sieves repurposed as moisture adsorbents for compressed oxygen gas. The spent adsorbents are collected from a Phase Technology Freezing Point analyzer after saturation is achieved through repeated operational cycles. Two thermal regeneration methods are  investigated, namely (1) staged heating in a furnace at 350 °C for 2 hours followed by a 30-minute vacuum treatment, and (2) staged heating in a gas chromatography (GC) oven at 350 °C with a dry-nitrogen purge for an hour, followed by another 1 hour without purging and a 30-minute vacuum duration. Furthermore, the physical characteristics after regeneration are assessed using the UOP Method 422 for particle size distribution (PSD) through micromesh sieving. Moisture adsorption performance is evaluated according to ASTM D1142 using a dew-point measurement with compressed oxygen at operating pressures and flow rates of 30–50 psi and 0.5–1.0 L/min, respectively. The results indicate that regenerated molecular sieves retain approximately 80–90% of the adsorption capacity of new material, which demonstrates that the GC-oven regeneration method exhibits slightly superior performance compared to furnace regeneration. These finding prove that appropriate thermal regeneration enables effective reuse of spent molecular sieves, providing a technically viable and economically favorable strategy for moisture removal in oxygen-drying applications while reducing laboratory waste.